Невзаємний фотонно-кристалічний хвилевід з феритовими елементами - Нєвров, В. Ю. (ХНУРЕ, 2022)
Photonic crystal waveguide with ferrite elements is considered. Numerical investigations of electrodynamic characteristics of the waveguide are performed on base of packages MPB and MEEP using. Dispersion characteristics and spatial distributions of the electromagnetic field components are calculated. One-way guiding due to effect of external magnetic field is shown by means of band diagrams and time scaling calculations.